Operation Strategy of Central Air Conditioning Virtual Power Plant Based on Risk Measurement Method - Guo, Mingxing; Guo, Xuxin; Yang, Jianlin; Gao, Ciwei; Chen, Tao (Frontiers in Energy Research, 2021)
Virtual power plant is an integrated technology and operation mode to enable air-conditioning load participating in power system operation. However, the principle of multi-system coupling in central air-conditioning poses quite a lot of challenges to conventional load regulation. At the same time, the uncertainties of demand-side resources bring risks to the operation of virtual power plant. In this paper, the load regulation characteristics of central air conditioning are obtained by various experimental study, and the potential of central air conditioning is also quantified by thermodynamic model. In this way, the central air conditioning model is transformed into a virtual unit model. Then the dynamic capacity optimization strategy is formulated based on the risk measurement theory, and the generation task decomposition strategy is formulated according to the equal increase rate criterion, thus forming a two-tier operation strategy of virtual power plant. Finally, some simulation study and typical experimental examples are constructed to quantitatively analyze the power generation capacity and effectiveness of the virtual power plant, which is also used to verify the effectiveness and practicability of the proposed method.